A botanical expedition in Eastern Alborz (Iran): rare plant species and assessing their conservation status - Rahnama, Fateme; Naderi, Reza; Amirahmadi, Atefe; Noroozi, Jalil; Mahmoodi, Mohammad; Mirtadzadini, Mansour (Phytotaxa, 2024)
This study is a part of an ongoing floristic study in Eastern Alborz mountain range (Iran). The flora and vegetation of this area are less known compared to those of Central Alborz. The study area indicates the regionally significant connection between the Kopet Dagh-Khorassan and Central Alborz. A total of 41 rare-threatened taxa belonging to 26 genera and 15 families are presented. According to the IUCN criteria, our checklist identifies 3 taxa classified as Critically Endangered (CR), 19 taxa as Endangered (EN), 4 taxa as Vulnerable (VU), 4 taxa as Near Threatened (NT), 3 taxa as Least Concern (LC), and 8 taxa as Data Deficient (DD). Among them, 28 are hemicryptophytes, followed by chamaephytes (7 species), geophytes (4 species), and therophytes (2 species). During 10 years of field investigations on the semi-arid areas of Eastern Alborz, some rare-threatened endemic species have been rediscovered in the region. Geographic distribution maps of all rare species together with the accompanying species and their conservation status were drawn up. It is noteworthy that some rare species are known only from their locus classicus and no new specimens have been collected during the last 30 to 80 years. A total of 10 taxa were reported for the first time from Eastern Alborz, primarily exhibiting a disjunct distribution pattern occurring in the high elevations of Zagros, Alborz and/or other mountain ranges in SW Asia.